Designing remote operations strategies to optimize science mission goals: Lessons learned from the Moon Mars Analog Mission Activities Mauna Kea 2012 field test. (August 2015) - Yingst, R.A.; Russell, P.; ten Kate, I.L.; Noble, S.; Graff, T.; Graham, L.D.; Eppler, D.
Abstract: The Moon Mars Analog Mission Activities Mauna Kea 2012 (MMAMA 2012) field campaign aimed to assess how effectively an integrated science and engineering rover team operating on a 24-h planning cycle facilitates high-fidelity science products. The science driver of this field campaign was to determine the origin of a glacially-derived deposit: was the deposit the result of (1) glacial outwash from meltwater; or (2) the result of an ice dam breach at the head of the valley? Lessons learned from MMAMA 2012 science operations include: (1) current rover science operations scenarios tested in this environment provide adequate data to yield accurate derivative products such as geologic maps; (2) instrumentation should be selected based on both engineering and science goals; and chosen during, rather than after, mission definition; and (3) paralleling the tactical and strategic science processes provides significant efficiencies that impact science return. The MER-model concept of operations utilized, in which rover operators were sufficiently facile with science intent to alter traverse and sampling plans during plan execution, increased science efficiency, gave the Science Backroom time to develop mature hypotheses and science rationales, and partially alleviated the problem of data flow being greater than the processing speed of the scientists. Highlights: We tested how effectively rover science operations facilitate high-fidelity science. The scenarios tested provide adequate data to yield a geologic map. Rover instruments should be chosen during, rather than after, mission definition. Paralleling tactical and strategic science tasks provides significant efficiencies.